2019
DOI: 10.1016/j.ejphar.2019.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate disposition, anti-folate activity and efficacy in the collagen-induced arthritis mouse model

Abstract: Methotrexate (MTX) efficacy in autoimmune arthritis is variable and unpredictable resulting in the need for the identification of biomarkers to guide drug therapy. This study utilizes the collageninduced arthritis mouse model to investigate erythrocyte MTX disposition and anti-folate activity as biochemical markers of efficacy in autoimmune arthritis. Following induction of arthritis, DBA/1J mice were treated with once-weekly subcutaneous MTX at varying doses over a period of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 57 publications
4
24
1
1
Order By: Relevance
“…In particular, several markers of pyrimidine and purine biosynthesis, including deoxyuridine monophosphate, 2‐deoxycytidine, 2‐deoxyuridine, and IMP may represent highly sensitive markers of MTX activity. These findings are consistent with previous studies that have found MTX treatment is associated with systemic depletion of circulating folates and corresponding dysregulation of intermediates of nucleotide metabolism …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In particular, several markers of pyrimidine and purine biosynthesis, including deoxyuridine monophosphate, 2‐deoxycytidine, 2‐deoxyuridine, and IMP may represent highly sensitive markers of MTX activity. These findings are consistent with previous studies that have found MTX treatment is associated with systemic depletion of circulating folates and corresponding dysregulation of intermediates of nucleotide metabolism …”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with previous studies that have found MTX treatment is associated with systemic depletion of circulating folates and corresponding dysregulation of intermediates of nucleotide metabolism. 18,28,29,41 Additional metabolites outside of folate and nucleotide metabolism displayed a high sensitivity to MTX. These metabolites included a metabolic intermediate of valine metabolism (i.e., ketoisovaleric acid) and several sugars, including galactose and fructose.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 15 These polymorphisms are challenging to study in a murine model given that a universal knockout of Rfc1 results in embryonic death 49 and DBA/1J mice are deficient in the formation of MTX polyglutamates. 50 Currently, there is an ongoing clinical trial by the CARRA Group (PROMOTE) to investigate PGx variant genomewide associations with MTX polyglutamates, toxicity, and therapeutic outcomes in patients with JIA; this work could provide additional support for examining the effect of variation in SLCO1B1 and several key PGx genes of interest on MTX response and toxicity in adults with RA or patients with other autoimmune diseases that are treated with low‐dose MTX (e.g., inflammatory bowel disease and psoriasis).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma MTX level is not a reliable predictor for adverse events in MTX therapy [ 132 ]. On the contrary, circulating folate levels and folate polyglutamate distribution change sensitively with MTX exposure and exogenous folate supply [ 133 ] and could be used as a biomarker of MTX efficacy [ 107 ]. It should be noted that as erythrocytes have a half-life of approximately 120 days, the results of blood examinations might reflect both pretreatment and posttreatment status, which need to be analyzed carefully [ 99 ].…”
Section: Discussionmentioning
confidence: 99%